NIGER DELTA MINORITIES AND THE QUEST FOR SOCIAL JUSTICE (2014)
The perceived inequitable distribution of economic and social resources remains a perennial feature of Nigeria’s political history. The rise of ethnic minority organisations and the concomitant violent struggles for justice has continued to militate against economic growth and political stability of Nigeria. Although, there are several studies on the conflicts and intervention programmes in the Niger Delta, these have not been done from the perspective of a Theory of Justice. This study, examined the agitation in the Niger Delta region as a quest for social justice. Rawls’s theory of ‘justice as fairness’ provided the analytical framework for this study. Four out of the six States of the Niger Delta were purposively selected. Questionnaire was administered to proportionate to size cross-section of youths and community leaders, purposively selected from three Local Government Areas (LGAs) in each of the four States: Rivers 250 (190:60), Delta 250 (190:60), Bayelsa 150 (100:50) and Edo 150 (100:50). Data were collected on the socio-demographic characteristics; perceptions of economic marginalisation, social amenities, resource control, unemployment, corruption and government policy on Niger Delta demands. Key informant interviews (KIIs) were conducted among three of each political office holders; academics; leaders of ethnic associations and Directors of Minority Rights non-governmental organisations. Quantitative data were analysed using descriptive statistics and ANOVA while qualitative data were content analysed. Age of the respondents was 34.2±12.1 years and 67.7% were males. Seventy-one percent were youths, while 44.8% had tertiary education. Perceptions of youths and community leaders on economic marginalisation varied from125:31 (63.4%) in Rivers to 97:37 (91.2%) in Bayelsa State; scarce social amenities varied from 74:21 (69.4%) in Edo to 158:38 (83.7%) in Delta States as major factors for persistent agitations for justice. Factors identified for violent agitation in the Niger Delta included: inability to control resources which varied from 83:22 (76.6%) in Edo to 174:38 (90.6%) in Delta; and a high level of unemployment from 61:23 (61.3%) in Edo to 97:26 (89.8%) in Bayelsa State. Perception of corruption among the elites, which varied from 148:49 (80.1%) in Rivers to 170:32 (86.3%) in Delta State, was identified as a major factor for government’s failure to address Niger Delta demands. There was a significant difference among the States regarding implementation of government policy on economic control of resources. Most respondents (93.6%) agreed to the need to promote a fair socio-economic distribution of resources among ethnic groups. There were significant differences regarding trust in government affirmative programmes and minority quest for justice. Infrastructural development and employment of youths were cited by most respondents (90.7%) as means of reducing the tendency for violent struggles. The KIIs indicated that inadequate premium on derivation principle and oppressive state policies led to socio-economic marginalisation of minority groups. Fair treatment of all groups would facilitate ethno-regional growth, while compensation, environmental and participatory justice would encourage equity and promote justice. Perceived marginalisation is central to the persistent quest and struggles for social justice in the Niger Delta region. Pragmatic approach should be taken to ensure equity in the distribution of resources.